Life and loss: the bittersweet moments of growing up with a long-term condition. (2nd November 2020) - Phillips, Hannah
Abstract : In this month's patient story, Hannah Phillips reflects on what her condition has taught her about life and loss, expressing the need for more open discussion of this topic among both patients and staff.